CONSERVATION STATUS AND PROPAGATION OF Camellia dalatensis AND Camellia capitata BY CUTTINGS - En Le Hong; Duong Do Van; Doan Nguyen Pham; Phuc Nguyen Van; Cam Ngo Van; Hoa Le Thi Thuy; Trung Nguyen Ba; Hung Ho Si; Phi Ngo Giang; Nguyen Nguyen Thanh; Truong Hoang Thanh; Cuong Truong Quang (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlights - Camellia dalatensis and Camellia capitata are critically endangered species. - Habitat loss and deforestation threaten the survival of these Camellia species. - Vegetative propagation aids conservation of critically endangered Camellia species. - Rooting success depends on cutting types, growth regulators, and substrate mix. - Research aids conservation efforts for Vietnam’s rare and vulnerable flora.